Cognitive Analytic Therapy for psychosis: A case series. (2nd May 2018) - Taylor, Peter J.; Perry, Alex; Hutton, Paul; Tan, Ranil; Fisher, Naomi; Focone, Chiara; Griffiths, Diane; Seddon, Claire
Abstract : Objectives: Cognitive Analytic Therapy (CAT) is an effective psychological intervention for several different mental health conditions. However, whether it is acceptable, safe, and beneficial for people with psychosis remains unclear, as is the feasibility of providing and evaluating it within a research context. The aim of this study was to begin to address these questions and to obtain for the first time a rich and detailed understanding of the experience of receiving CAT for psychosis. Design: A mixed‐methods case series design. Method: Seven individuals who experienced non‐affective psychosis received CAT. They completed assessments at the start of CAT, 16 weeks, and 28 weeks post‐baseline. Qualitative interviews were completed with four individuals following completion of or withdrawal from therapy. Results: Six participants attended at least four sessions of therapy and four went on to complete therapy. There were no serious adverse events, and self‐reported adverse experiences were minimal. Qualitative interviews suggested CAT is acceptable and provided a way to understand and work therapeutically with psychosis. There was limited evidence of change in psychotic symptoms, but improvement in perceived recovery and personality integration was observed. Conclusions: The results suggest that CAT is a safe and acceptable intervention for psychosis. Personality integration, perceived recovery, and functioning are relevant outcomes for future evaluations of CAT for psychosis. Practitioner points: It is feasible to conduct research evaluating CAT for people with psychosis. Within this case series, CAT appears acceptable and safe to individuals with psychosis. Within this case series, clients reported that CAT was a positive and helpful experience. There is a mixed picture with regard to secondary outcomes, but the design and aims of this case series limit conclusion that can be drawn from this data.